Organic matter from biofilter nitrification by high performance size exclusion chromatography and fluorescence excitation-emission matrix - E.N. Hidayah; W.L. Lai; O.H. Cahyonugroho; F. Rizqa (Global Journal of Environmental Science and Management)
A combination of high performance size exclusion chromatography with organic carbon detector and ultraviolet detector coupled with peak-fitting technique and fluorescence excitation-emission matrix spectrometry applied fluorescence regional integration method was conducted to determine the characteristics of organic matter during nitrification. The batch scale of bionet nitrification without organic carbon substrate under aerobic conditions was operated for around 150 minutes. Bulk organic parameters and NH4+-N concentration were analyzed. Five different molecular weights of organic matter were identified by using chromatography, and five different groups of fluorophores organic fractions detected by fluorescence. According to chromatography with carbon and ultraviolet detector, the main characteristics of organic matter shifted from building blocks aromatic compounds with percentage peak area of carbon/ultraviolet detector: 31%/53% to 14%/27.5% to humic-like substances with percentage peak area of carbon/ultraviolet detector 21%/17% to 27%/46.5% during nitrification. Those former compounds are biodegradable as well as properties of microbial products released during substrate utilization and endogenous phase, which are mainly identified as humic-like substances, thus underwent further biodegradation. However, there was significant change in the fluorophores organic fractions, which exhibited humic acid-like with percentage fluorescence regional index area 53% into 68%, as shown by fluorescence excitation-emission matrix analysis. A combination of these methods indicated that the organic matter released during nitrification mainly consists of humic compounds. These results conjecture that a combination of high performance size exclusion chromatography with carbon and ultraviolet detector and fluorescence excitation-emission matrix can be used to determine the characteristic of organic matter and water quality change during nitrification.